1D tungsten oxide nanostructures on a Cu(1 1 0) surface. (23rd October 2018) - Šedivá, Romana; Pistonesi, Carolina; Pronsato, María E; Duchoň, Tomáš; Stetsovych, Vitalii; Mysliveček, Josef; Mašek, Karel
Abstract: Thin epitaxial layers of tungsten oxide on metal substrates are suitable as model systems for investigation of chemical reactivity and catalytic properties. However, the ability to prepare epitaxial tungsten oxide model system in situ is quite rare. Here we present a method to prepare highly ordered tungsten oxide thin film on a Cu(1 1 0) single crystal substrate using physical vapor deposition in a reactive atmosphere of atomic oxygen. The oxygen induced reconstruction of the copper substrate gives rise to unique self-organized 1D structures of tungsten oxide parallel with the Cu[1 −1 0] crystallographic direction. Utilizing a combination of photoemission spectroscopy and density functional theory calculations we reveal emergent physicochemical properties related to the low-dimensionality of the system. Specifically, we observe a support mediated charge redistribution at the interface and a momentum dependent modulation of the valence-band electronic structure. The unusual character of the 1D oxide nanostructures on Cu(1 1 0) surface opens up a unique avenue for preparation of tungsten oxide-based functionalized nanostructures and provides options for further investigation of the fundamental properties of tungsten oxide.